"Caracterización de árboles dispersos en fincas ganaderas en la zona centro-norte de los Ríos, Ecuador. - Romero Sánchez, Genaro Marcelo (2020)
The research was carried out in the North Central Zone of the province of Los Ríos (Quevedo, Mocache, Palenque, Ventanas, Buena Fe and Valencia), and the objective of this was to know the socioeconomic situation of the cattle producers, to characterize the trees dispersed in pastures of the cattle farms, as well as to value the edaphic state of each visited zone. To do this, it was necessary to carry out a structured interview to learn about the socioeconomic situation of producers, as well as a tour of the farm to identify the different species of trees and shrubs present in the pastures, evaluate the distance between trees, shaft height, diameter at breast height (DAP), total height, crown area, and the alpha and beta diversity of the species. Finally, soil analyses were carried out that allowed estimating the richness and texture of each one of them. The results show that the current socioeconomic situation of producers requires greater assistance, which will allow them and the following generations to remain in this activity. Regarding the characterization of dispersed trees, 13 families and 23 species were identified, of which 11 species were found in the Palenque canton, being this the most diverse. Simpson's index for the study zone was 0.68 and Shanon's 1.59. Beta diversity indicates similarity between Ventanas, Palenque, Buena Fe and Valencia cantons. Finally, soil analysis determined that soils with higher macro and micro nutrient content are found in Ventanas canton, while soils with higher organic matter content are found in Valencia canton. Keywords: Diversity, tree density, agroforestry, sustainable livestock.